2005
DOI: 10.1207/s15374424jccp3401_9
|View full text |Cite
|
Sign up to set email alerts
|

Home Chaos: Sociodemographic, Parenting, Interactional, and Child Correlates

Abstract: We conducted 2 studies to (a) establish the usefulness of the construct of home chaos, (b) investigate its correlates, and (c) determine the validity of the Confusion, Hubbub, and Order Scale (CHAOS) used to measure the construct in each study. Study 1 relied on a sample of European American preschoolers and their mothers and Study 2 on a sample of African American school-age children and their caregivers. Home chaos was associated with less effective parental discipline; elevated behavior problems, limited at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
268
3
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(309 citation statements)
references
References 35 publications
25
268
3
5
Order By: Relevance
“…Specifically, parents who reported higher levels of chaos in the home were more likely to report clinically elevated levels of externalizing behaviors in their children. This is consistent with the original, English version of the CHAOS that has been shown to have good reliability and positive correlations with parenting stress and child externalizing behaviors (Dumas et al 2005).…”
Section: Psychometric Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…Specifically, parents who reported higher levels of chaos in the home were more likely to report clinically elevated levels of externalizing behaviors in their children. This is consistent with the original, English version of the CHAOS that has been shown to have good reliability and positive correlations with parenting stress and child externalizing behaviors (Dumas et al 2005).…”
Section: Psychometric Propertiessupporting
confidence: 86%
“…Thus, the goal of the current study was to establish both the psychometric and cultural properties of several Spanish versions of measures commonly used in comprehensive ADHD assessments. Specifically, the present study examined the psychometric and cultural properties of the Spanish translations of the Parenting Sense of Competence (PSOC; as cited in Johnston and Mash 1989), Alabama Parenting Questionnaire (APQ; Shelton et al 1996), and Confusion, Hubbub, and Order Scale (CHAOS; Dumas et al 2005). …”
Section: Current Studymentioning
confidence: 99%
“…(12) found that children reared in inconsistent home environments lacking in routine and organization tended to display more conduct problems. Among caregivers, perceptions of disruption in the home are related to less effective discipline (13), fewer supportive responses by caregivers to children's negative emotions (14), higher stress, and lower warmth (15). The Sesame Street materials, tested during this research, are designed to improve vital caregiver and child interactions during times of stress.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the interrelationship between the perceived home instability and low levels of child intelligence is reported (Dumas et al, 2005), as well as high level of behavioral disorders (Petrill et al, 2004). As reported in a longitudinal study of the direction of effects of family environment and child intelligence, the perceived family environment instability influences low intelligence in children (DeaterDeckard et al, 2009).…”
mentioning
confidence: 95%
“…In the studies on the links between parenting and children's cognitive abilities, the family environment is traditionally analyzed through child's perceptions of family stability/chaos (Dumas et al, 2005). As an example, the interrelationship between the perceived home instability and low levels of child intelligence is reported (Dumas et al, 2005), as well as high level of behavioral disorders (Petrill et al, 2004).…”
mentioning
confidence: 99%